Effect of quercetin and role of nitric oxide pathway in chloroquine-induced scratching - Osman Kukula; Caner Günaydin (Universidade de São Paulo, 2023)
Abstract Nitric oxide (NO) is an abundant mediator which is demonstrated to be involved in pruritus. Assuming that the increased NO also mediates chloroquine-induced pruritus, which is a frequent complication seen in the chronic chloroquine treatment, the current study aimed to investigate the effect of quercetin and the role of NO in chloroquine-induced pruritus in C57BL/6 mice. Model was created with subcutaneous chloroquine (400µg/site) injection to the nape of the mice. Effect of quercetin and role of NO were investigated with administration of quercetin, and co-administration with L-NAME, 7-NI and L-arginine before chloroquine injection. Locomotor activity was assessed by activity cage and number of the scratching bouts after chloroquine injection was recorded for 30 minutes. Our results show that quercetin significantly reduced scratching bouts at the doses of 10, 20, 40 and 80 mg/kg. Locomotor activity was decreased at the 40 and 80 mg/kg doses of quercetin. Additionally, decrease of the number of scratching bouts by quercetin prevented by L-arginine treatment, while L-NAME and 7-NI enhanced the anti-pruritic effect of sub-effective doses of quercetin. Therefore, our study demonstrated that acute injection of quercetin significantly diminished chloroquine-induced scratching behavior, and this effect is partly mediated by inhibition of neuronal nitric oxide synthase enzyme.